Answer:
The average rate of change from x = −2 to x = 0 is 3.
Step-by-step explanation:
The given function is,
[tex]f(x)=2x^3+x^2-3x+1[/tex]
Put x=-2,
[tex]f(-2)=2(-2)^3+(-2)^2-3(-2)+1=-5[/tex]
Put x=0
[tex]f(0)=2(0)^3+(0)^2-3(0)+1=-1[/tex]
From the graph of f(x) it is noticed that the graph passing through (-2,-5) and (0,2).
Average rate of change is the change is function with respect to x.
[tex]m=\frac{f(x_2)-f(x_1)}{x_2-x_1}[/tex]
[tex]m=\frac{f(0)-f(-2)}{0-(-2)}[/tex]
[tex]m=\frac{1-(-5)}{2}[/tex]
[tex]m=\frac{1+5}{2}[/tex]
[tex]m=\frac{6}{2}[/tex]
[tex]m=3[/tex]
Therefore the average rate of change from x = −2 to x = 0 is 3.